Knowledge and Meaning. On the New Illiteracy from a Hermeneutical Perspective: Array - Afloroaei, Stefan (Acta Universitatis Danubius. Communicatio, 2021)
Knowledge and Meaning. On the New Illiteracy from a Hermeneutical Perspective. Many life situations and especially communication situations tell us that we should not mistake an ordinary piece of information for knowledge proper or for a meaning proper. These three types of intentionalities – to inform, to know and to understand – are very different, although they continuously interfere. Man’s specific capacity of understanding appears to us now more important than others. In the absence of a good exercise of understanding, information can remain either strange, or indifferent to us. Man can become informed or even a connoisseur, but still, an alien to those elevated landmarks – moral or human, cultural – which make possible a good self-orientation. This fact is directly connected to what is called nowadays “functional illiteracy”. Actually, this concerns particularly the capacity of understanding something said or done. For this reason, this can be considered a case of illiteracy of hermeneutical nature. The pedagogical solution for such a phenomenon involves continuously practising the competence of understanding. Thus, it would be absolutely normal to focus on understanding, and not on information and, further on, on self-understanding and understanding the other, instead of focusing on an ordinary phenomenon. Consequently, cultivating the senses and the mind, for a better orientation in the world of life, is more important than the technical efficiency of the learning process.